A qualitative investigation of recovery after femoral fracture in Rett syndrome. (11th August 2016) - Horne, T.; Leonard, H.; Stannage, K.; Downs, J.
Abstract: Background: Children with severe disability often develop osteoporosis and have an increased risk of fracture. In Rett syndrome, the prevalence of fracture is four times greater than in the general population, and the femur is commonly affected. This study used qualitative methods to investigate the regaining of mobility within 12 months following femoral fracture in Rett syndrome and parent caregiver experiences. Methods: Caregivers ( n = 14) of cases registered with the Australian Rett Syndrome Database with a daughter with Rett syndrome were recruited if their daughter sustained a femoral fracture between 2009 and 2014. Median (interquartile range) age at fracture was 11 years and 4 months (8 years and 8 months to 22 years and 3 months). Qualitative methods were used to investigate parent/caregiver experiences and their daughter's recovery following fracture. Themes in the interview data were identified with thematic analysis. Results: Operative management was chosen for those walking independently and non‐operative management for most of the remaining. All who walked independently and one of the four who required assistance recovered pre‐operative walking skills within 6 months. Themes identified by caregivers related to the complexities of pain recognition, the caregiver emotional journey and later rebuilding of relationships with service providers. Conclusions: Those who walked with assistance were vulnerable to loss of this skill. Difficulties in pain recognition increased time to diagnose fracture, and the acute episode was associated with heightened caregiver stress. Service providers can use family‐centred practice models to support the strengthening of family functioning following this acute event that is surprisingly common in those with severe disability.